Design, Objects and Memory: A Sustainability-Oriented Project Itinerary - Torres, Myrla (2021)
Game kasino Concerns related to sustainability are recurrent in Design. Questioning project practices, reassessing principles which are intrinsic to the design process, promoting the dissemination of sustainability-oriented actions, and contributing with a new awareness-raising process about consumption are attitudes that might help in the inclusion of environmental and social requirements in design practices. The relationship between sustainability and esthetic, symbolic and affective aspects is under explored in project elaboration. The project process that emphasizes subjective and material characteristics of objects with a view towards the appreciation of affective memories, through the analysis of users’ real-life experiences, might allow the designer to rethink time, tradition, aesthetics and perception to comprehend characteristics at play that are emotionally sustainable. This paper presents and discusses the ongoing research, whose main objective is to design a sustainability-oriented project itinerary, through affections and memory embedded into the relationship between people and objects.